Optimal Solution Algorithm for Transport Problem With practical application - Afraa Abbas Hamada (Genius Journals, 2023)
Transportation problem is an important mathematical method in the decision-making process in transferring the quantity of goods from the sources of manufacturing to the centers requested at the lowest possible cost. In this research, a model was presented for the transport problem, and this model was solved by using the exponential method to find the optimal solution for the transport problem. This method is considered as a modern and important method for economic and service decision makers for the production facilities. For the purpose of comparing the results using WIN.QSB, to solve the problem of transferring the black oil product from the warehouses to the governorates requesting the product of the intermediate refineries, good results were achieved in reducing the cost of transportation. After the implementation of the exponential method came at a total cost of (113225) ID. The results of the method of solving the linear programming amounted to (111075) ID
Keywords: The optimal Solution; The exponential method